2008
DOI: 10.1016/j.jaci.2008.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a role for B cell–activating factor of the TNF family in the pathogenesis of chronic rhinosinusitis with nasal polyps

Abstract: Overproduction of BAFF in nasal polyps may contribute to the pathogenesis of CRSwNP via the local induction of IgA and activation of eosinophils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
168
1
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 165 publications
(186 citation statements)
references
References 45 publications
14
168
1
3
Order By: Relevance
“…In addition, our group has previously shown that B cell-activating factor (BAFF) of the TNF family, a key B cell survival factor, is highly expressed in NP tissue from patients with CRSwNPs (8). We also reported increased levels of autoantigen-specific antibodies in NP tissue (9,10).…”
Section: Clinical Relevancementioning
confidence: 83%
“…In addition, our group has previously shown that B cell-activating factor (BAFF) of the TNF family, a key B cell survival factor, is highly expressed in NP tissue from patients with CRSwNPs (8). We also reported increased levels of autoantigen-specific antibodies in NP tissue (9,10).…”
Section: Clinical Relevancementioning
confidence: 83%
“…528 In addition to host defense molecules, ECs respond to PRR stimulation with the secretion of cytokines and chemokines that foster inflammation and attract and activate innate effector cells. 362,515,[529][530][531][532] In addition, the EC cytokines play a key role in shaping any subsequent adaptive immune response. Cytokine crosstalk between ECs, innate lymphoid cells (ILCs), and dendritic cells matches the appropriate innate and adaptive response to particular foreign stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…288,556 These observations suggest that host defects in CRS will be centered in the airway mucosa, giving rise to the "immune barrier hypothesis," which proposes that genetic and epigenetic variation in the coordinated mechanical barrier and/or the innate immune response of the sinonasal epithelium manifests as CRS. 530 Diminished innate host defense coupled with a porous barrier should theoretically lead to altered microbial colonization, accentuated barrier damage, and a compensatory adaptive immune response. 491,528 Although somewhat distinct, CRSsNP and CRSwNP both exhibit innate immune and mechanical barrier defects.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry was performed as described previously (15). Briefly, blocked sections were incubated with antihuman fibrin antibody (Sekisui Diagnostics, Stamford, CT) or antihuman t-PA antibody (Sigma, St. Louis, MO) at 4 8 C overnight.…”
Section: Immunohistochemistrymentioning
confidence: 99%